Third construction (1941) - Cage, John 1912-1992 (Mode Records, 2012)
"Cage's vision of the future of music was first shaped by an intense creative period from 1935-1942, when he wrote many of the seminal works for percussion ensemble featured here." - Container
Aufnahmen: 26.-28. und 30. Juni 2011, Boutell Memorial Concert Hall, Northern Illinois University, DeKalb, IL; 29. Juni 2011, Ruth Ford House, Aurora, IL (Living room music)
Works for percussion sextet, trio, or quartet; the 2nd movement of Living room music for speech quartet, words by Gertrude Stein
Program notes by Gregory Beyer and David Skidmore in English with French and German translations (16 p. ; 12 cm) inserted in container
Keywords: Percussion ensembles; Vocal quartets with percussion; Stein, Gertrude / 1874-1946 / Musical settings; Stein, Gertrude / 1874-1946; CD